2021
DOI: 10.1152/advan.00106.2021
|View full text |Cite
|
Sign up to set email alerts
|

Core concepts in physiology: teaching homeostasis through pattern recognition

Abstract: Homeostasis is a core concept in systems physiology that future clinicians and biomedical professionals will apply in their careers. Despite this, many students struggle to transfer the principles governing homeostasis to concrete examples. Precourse assessments conducted on 72 undergraduate biology students enrolled in an introductory systems physiology course at the University of Belgrade during the February–May semester of 2021 revealed that students had a vague, fragmentary understanding of homeostasis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 55 publications
1
2
0
Order By: Relevance
“…Student interviews indicated that the novel scenarios were indeed more successful in eliciting HOCS ( 11 ). This qualitative result provides some empirical support for others’ stated preferences for unfamiliar scenarios in summative assessments (e.g., 12 15 ).…”
Section: Introductionsupporting
confidence: 58%
“…Student interviews indicated that the novel scenarios were indeed more successful in eliciting HOCS ( 11 ). This qualitative result provides some empirical support for others’ stated preferences for unfamiliar scenarios in summative assessments (e.g., 12 15 ).…”
Section: Introductionsupporting
confidence: 58%
“…Furthermore, as the ensemble starts to interact with other ensembles, it becomes a structure like an orchestral ensemble where the interactions between different sections of the orchestra are extremely sensitive and intricate to form some kind of homeostasis usually led by a conductor. The model is intentionally reductive and can be made more specific by exploring additional physical examples such as the seven-step model (stimulus, receptor, input, integrating center, output, effector, and response) presented by Chirillo et al (2021). Still, we think it is also essential to try to pin down the core patterns from complex processes to get an overview and understanding of the discussed rhythms in this article at a macroscale.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting conceptual model can be formulated using the terms found in brackets (sensor, control center, effector; Modell et al, 2015) and comprises a proper elaboration of textbook's conceptual learning objectives. The sensor, control center, and effectors may be physically far from each other in the body and represent the components of a typical control system (Chirillo et al, 2021). Students can use these terms to think about how the human body remains constant despite the higher environmental temperature.…”
Section: Final Statementioning
confidence: 99%